Statins and gastroesophageal reflux disease: A meta-analysis - K. Wijarnpreecha (2020)
Background/Objectives: Gastroesophageal reflux disease (GERD) is one of the common gastrointestinal disorders worldwide. Recent epidemiologic studies have suggested that use of statins may lower the risk of GERD although the results from different studies were inconsistent. This systematic review and meta-analysis were conducted with the aim to summarize all available data. Methods: A systematic literature review was performed using MEDLINE and EMBASE database from inception to December 2017. Cohort, case-control, and cross-sectional studies that compared the risk of GERD among statin users versus nonusers were included. Pooled odds ratio (OR) and 95% confidence interval (CI) were calculated using a random-effect, generic inverse variance method. Results: A total of 4 studies (1 case control, 1 cohort, and 2 cross-sectional studies) with 14,505 participants met the eligibility criteria and were included in the meta-analysis. The risk of GERD among statin users was numerically lower than nonusers with the pooled OR of 0.89 but the result did not achieve statistical significance (95% CI, 0.60-1.33). The statistical heterogeneity in this study was moderate (I2 = 54%). Conclusions: The current meta-analysis found that the risk of GERD was numerically lower among statin users although the pooled result did not reach statistical significance. Therefore, more studies are still needed to further clarify this potential benefit of statins.